INDONESIA - INDIA DEFENSE DIPLOMACY IN THE INDIAN OCEAN - Marina Ika Sari; Leonard F. Hutabarat; Amarulla Octavian (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2018)
Abstract - This study focuses on defense diplomacy between Indonesia and India in the Indian Ocean. This study used defense diplomacy concept and qualitative method with Soft System Methodology (SSM) and NVivo for the analysis technique. The data was collected through interviews and literature study. The results show that Indian Ocean has become important region in the geopolitic in the 21st century. Indonesia and India view the Indian Ocean as their strategic environment. Diplomatic ties between Indonesia and India have built since 1951 and enhanced with Strategic Partnership open the opportunity for both countries to conduct defense diplomacy in the Indian Ocean. Forms of defense diplomacy between Indonesia and India are through Biennial Defense Minister Forum, Joint Defence Cooperation Committee (JDCC), Navy to Navy Talk, India-Indonesia Coordinated Patrol (Ind-Indo Corpat). The defense diplomacy activities aim to improve the Confidence Building Measures (CBM) and the defense capability.